Estimating the effect of plant‐provided food supplements on pest consumption by omnivorous predators: lessons from two coccinellid beetles. Issue 5 (2nd September 2016) - Schuldiner‐Harpaz, Tarryn; Coll, Moshe
Abstract: BACKGROUND: Plant‐provided food supplements can influence biological pest control by omnivorous predators in two counteracting ways: they can (i) enhance predator populations, but (ii) reduce pest consumption by individual predators. Yet the majority of studies address only one of these aspects. Here, we first tested the influence of canola ( Brassica napus L. ) pollen supplements on the life history of two ladybeetle species: Hoppodamia variegata (Goeze) and Coccinella septempunctata (L.). We then developed a theoretical model to simulate total pest consumption in the presence and absence of pollen supplements. RESULTS: Supplementing a prey diet with canola pollen increased H. variegata larval survival from 50 to 82%, and C. septempunctata female oviposition by 1.6‐fold. Model simulations revealed a greater benefit of pollen supplements when relying on C. septempunctata for pest suppression than on H. variegata . CONCLUSION: For these two predators, the tested pollen serves as an essential supplement to a diet of prey. However, the benefit of a mixed prey–pollen diet was not always sufficient to overcome individual decrease in pest consumption. Taken together, our study highlights the importance of addressing both positive and negative roles of plant‐provided food supplements in considering the outcome for biological control efforts that rely on omnivorous predators. © 2016 Society of Chemical Industry